Induction of a Mesenchymal Expression Program in Lung Epithelial Cells by Wingless Protein (Wnt)/β-Catenin Requires the Presence of c-Jun N-Terminal Kinase–1 (JNK1) - van der Velden, Jos L. J. (American Thoracic Society, 2012)
Recent studies suggest the importance of the transition of airway epithelial cells (EMT) in pulmonary fibrosis, and also indicate a role for Wingless protein (Wnt)/β-catenin signaling in idiopathic pulmonary fibrosis. We investigated the possible role of the Wnt signaling pathway in inducing EMT in lung epithelial cells, and sought to unravel the role of c-Jun–N-terminal-kinase–1 (JNK1). The exposure of C10 lung epithelial cells or primary mouse tracheal epithelial cells (MTECs) to Wnt3a resulted in increases in JNK phosphorylation and nuclear β-catenin content. Because the role of β-catenin as a transcriptional coactivator is well established, we investigated T-cell factor/lymphocyte-enhancement factor (TCF/LEF) transcriptional activity in C10 lung epithelial cells after the activation of Wnt. TCF/LEF transcriptional activity was enhanced after the activation of Wnt, and this increase in TCF/LEF transcriptional activity was diminished after the small interfering (si)RNA-mediated ablation of JNK. The activation of the Wnt pathway by Wnt3a, or the expression of either wild-type or constitutively active β-catenin (S37A), led to the activation of an EMT transcriptome, manifested by the increased mRNA expression of CArG box-binding factor–A, fibroblast-specific protein (FSP)–1, α–smooth muscle actin (α-SMA), and vimentin, increases in the content of α-SMA and FSP1, and the concomitant loss of zona occludens–1. The siRNA-mediated ablation of β-catenin substantially decreased Wnt3a-induced EMT. The siRNA ablation of JNK1 largely abolished Wnt3a, β-catenin, and β-catenin S37a-induced EMT. In MTECs lacking Jnk1, Wnt3a-induced increases in nuclear β-catenin, EMT transcriptome, and the content of α-SMA or FSP1 were substantially diminished. These data show that the activation of the Wnt signaling pathway is capable of inducing an EMT program in lung epithelial cells through β-catenin, and that this process is controlled by JNK1.